Metachronous extraskeletal (soft tissue) epithelioid osteogenic sarcoma: a case report - Rawal, Gireesha (J Med Case Rep, 2019)
BACKGROUND: Metachronous osteosarcoma is a rare form of osteosarcoma. The occurrence of metachronous tumor in soft tissue is exceedingly rare. The pathogenesis of metachronous osteosarcoma, as to whether it represents multiple true primaries or metastatic disease, is still obscure. CASE PRESENTATION: A 49-year-old Indian man presented with progressively increasing swelling in his left hand of 2 months’ duration. An X-ray showed a soft tissue lesion. Contrast-enhanced computed tomography showed a soft tissue mass lesion, with peripheral enhancement and central necrotic areas in radial palmar soft tissue overlying second metacarpophalangeal region with no obvious bony osteolysis. Possibilities of acute abscess, resolving hematoma, or aggressive soft tissue mass lesion were suggested. An incision biopsy showed morphological features of epithelioid osteosarcoma, which was confirmed on immunohistochemistry. A detailed history revealed that our patient was diagnosed as having osteosarcoma of his right leg 3 years previously. Based on history, radiology, morphology, and immunohistochemistry, a final diagnosis of extraskeletal (soft tissue) epithelioid osteogenic sarcoma of the left hand occurring as a metachronous tumor 3 years after diagnosis of primary osteosarcoma in the right leg was given. CONCLUSION: This is probably the first reported case of extraskeletal (soft tissue) epithelioid osteosarcoma occurring as a metachronous tumor 3 years after diagnosis of primary osteosarcoma in the right leg. The prognosis of metachronous skeletal osteosarcoma is poor as compared to that of relapse limited to lungs. In late metachronous osteosarcoma, combined-modality therapy comprising surgery and aggressive chemotherapy may affect long-term survival. Lifelong follow-up of surviving patients with osteosarcoma is necessary and if metachronous osteosarcoma is discovered, it should be treated with curative intent. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13256-019-2070-3) contains supplementary material, which is available to authorized users.